Insight of reaction mechanism and anionic redox behavior for Li-rich and Mn-based oxide materials from local structure. (May 2021) - Zhuo, Haoxiang; Liu, Yang; Wang, Zhenyao; Zhang, Anbang; Li, Zhao; Ren, Zhimin; Liu, Xianghuan; Peng, Haoyang; Wang, Ligen; Shi, Jingmin; Sun, Xueyi; Lu, Shigang; et al.
Abstract: Li-rich and Mn-based oxides (LRMO) have been an obvious choice of high specific energy batteries owing to their unique anion redox behavior based on the main component Li2 MnO3 . However, there are still electrochemical behaviors that cannot perfectly match the theoretical structure. So far, most theoretical research on LRMO has been carried out around the ideal Li2 MnO3 structure. Nevertheless, there are a great number of non-ideal local configurations in the pristine materials under the case of practical situations. Herein, the ubiquitous complex local structures (defect-like) in the interior of Li2 MnO3 particle, some of which have not been observed in the past, are directly presented through the atomic-level observation. We summarized these structures and proposed for the first time the great influence of these local structures on the electrochemical and the oxygen redox behavior of LRMO by combining observation, DFT calculation, XAS, XPS and electrochemical experiments. These micro-structures have been roughly divided into four categories by the advanced AC-STEM, including the so-called stacking faults caused by the slip of the adjacent TM layer, the local multi-Li or multi-Mn arrangement due to the combination of different stacking type along a–b plane, the expansion of the interlayer spacing, and even the distribution of polycrystalline domains, of which the second and third configurations were observed for the first time. These types of local structures dominate the electrochemical reaction of electrodes in some aspects by improving the activity of oxygen non-bonding 2p states, along with the improvement of (de)intercalation ability for Li ions in the bulk through reducing the energy barrier, and they are even one of the sources of voltage hysteresis by affecting the energy level distribution of oxygen unoccupied 2p states after delithiation. This research has perfected a more comprehensive and practical understanding of LRMO under the case of practical situations, laying a key foundation for the further modification and application of LRMO cathode materials. Graphical Abstract: ga1 Highlights: The new revelation of complex local structures in the practical Li-rich and Mn-based oxides. The decisive influence of these local structures on the electrochemical behavior of anion redox and materials. Perfection of the theoretical system by combining DFT calculation with atomic-level observation and XAS. A new perspective for the future modification of Li-rich and Mn-based cathode materials.